Simultaneous Cervical and Lumbar Spinal Cord Stimulation Induces Facilitation of Both Spinal and Corticospinal Circuitry in Humans - Parhizi, Behdad; Barss, Trevor S.; Mushahwar, Vivian K. (Frontiers in Neuroscience, 2021)
Coupling between cervical and lumbar spinal networks (cervico-lumbar coupling) is vital during human locomotion. Impaired cervico-lumbar coupling after neural injuries or diseases can be reengaged via simultaneous arm and leg cycling training. Sensorimotor circuitry including cervico-lumbar coupling may further be enhanced by non-invasive modulation of spinal circuity using transcutaneous spinal cord stimulation (tSCS). This project aimed to determine the effect of cervical, lumbar, or combined tSCS on spinal reflex (Hoffmann [H-]) and corticospinal (motor evoked potential [MEP]) excitability during a static or cycling cervico-lumbar coupling task. Fourteen neurologically-intact volunteers were seated in a recumbent leg cycling system. H-reflex and MEP amplitudes were assessed in the left flexor carpi radialis (FCR) muscle during 2 tasks (Static and Cycling) and 4 conditions: (1) No tSCS, 2) tSCS applied to the cervical enlargement (Cervical); 3) tSCS applied to the lumbar enlargement (Lumbar); 4) simultaneous cervical and lumbar tSCS (Combined). While cervical tSCS did not alter FCR H-reflex amplitude relative to No tSCS, lumbar tSCS significantly facilitated H-reflex amplitude by 11.1%, and combined cervical and lumbar tSCS significantly enhanced the facilitation to 19.6%. Neither cervical nor lumbar tSCS altered MEP amplitude alone (+4.9% and 1.8% relative to legs static, No tSCS); however, combined tSCS significantly increased MEP amplitude by 19.7% compared to No tSCS. Leg cycling alone significantly suppressed the FCR H-reflex relative to static, No tSCS by 13.6%, while facilitating MEP amplitude by 18.6%. When combined with leg cycling, tSCS was unable to alter excitability for any condition. This indicates that in neurologically intact individuals where interlimb coordination and corticospinal tract are intact, the effect of leg cycling on cervico-lumbar coupling and corticospinal drive was not impacted significantly with the tSCS intensity used. This study demonstrates, for the first time, that tonic activation of spinal cord networks through multiple sites of tSCS provides a facilitation of both spinal reflex and corticospinal pathways. It remains vital to determine if combined tSCS can influence interlimb coupling after neural injury or disease when cervico-lumbar connectivity is impaired.